2018
DOI: 10.1016/j.ccell.2017.11.007
|View full text |Cite|
|
Sign up to set email alerts
|

β2 Adrenergic-Neurotrophin Feedforward Loop Promotes Pancreatic Cancer

Abstract: Catecholamines stimulate epithelial proliferation, but the role of sympathetic nerve signaling in pancreatic ductal adenocarcinoma (PDAC) is poorly understood. Catecholamines promoted ADRB2-dependent PDAC development, nerve growth factor (NGF) secretion, and pancreatic nerve density. Pancreatic Ngf overexpression accelerated tumor development in LSL-Kras;Pdx1-Cre (KC) mice. ADRB2 blockade together with gemcitabine reduced NGF expression and nerve density, and increased survival of LSL-Kras;LSL-Trp53;Pdx1-Cre (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
297
3
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(344 citation statements)
references
References 62 publications
10
297
3
3
Order By: Relevance
“…In addition to enhanced tumor angiogenesis, tumor innervation might further enhance tumorigenesis by enriching the tumor microenvironment with catecholamines released by the newly formed nerve endings. We and others have found that in response to catecholamines, tumor cells release neurotrophins (BDNF/NGF), which leads to increased tumor innervation and growth in restraint stress tumor models [59, 60]. There is evidence to show that behavioral stress contributes to an increase in catecholaminergic nerve fibers within lymphoid organs in primates, an indication of a long-term regulatory influence of stress on immune responses [61].…”
Section: Stress Inflammation and The Role Of Eicosanoidsmentioning
confidence: 99%
“…In addition to enhanced tumor angiogenesis, tumor innervation might further enhance tumorigenesis by enriching the tumor microenvironment with catecholamines released by the newly formed nerve endings. We and others have found that in response to catecholamines, tumor cells release neurotrophins (BDNF/NGF), which leads to increased tumor innervation and growth in restraint stress tumor models [59, 60]. There is evidence to show that behavioral stress contributes to an increase in catecholaminergic nerve fibers within lymphoid organs in primates, an indication of a long-term regulatory influence of stress on immune responses [61].…”
Section: Stress Inflammation and The Role Of Eicosanoidsmentioning
confidence: 99%
“…Large nerves are also observed in murine PDAC tumors and an increased intra-tumoral density of sympathetic nerves has been reported in enlarged tumors of Kras-mutant mice subjected to chronic stress conditions 8,14 . Stress-mediated upregulation of nerve growth factor (NGF) secretion by tumor cells was proposed to attract sympathetic nerve growth via "tumor axonogenesis" 8 .…”
Section: Introductionmentioning
confidence: 95%
“…The role of the sympathetic nervous system in PDAC has been studied in terms of tumor response to stress and has shown context-dependent effects. Experimental sympathectomy or blockade of badrenergic signaling in mouse models of PDAC abolishes the pro-tumor effect of chronic restraint stress, but also inhibits the anti-tumor effect of "eustress" (positive stress) induced by enriched housing conditions [8][9][10] . How the reactivity of the sympathetic nervous system to stressors can have opposing actions on tumor development is not clear, but it may involve differential regulation of immune cell functions (eustress) or direct effects on tumor cell growth (distress).…”
Section: Introductionmentioning
confidence: 99%
“…The study, published in Cancer Cell , also found that beta blockers, which inhibit the hormone epinephrine (adrenaline), increased survival in mice with the disease …”
mentioning
confidence: 96%
“…The study, published in Cancer Cell, also found that beta blockers, which inhibit the hormone epinephrine (adrenaline), increased survival in mice with the disease. 1 "We've been looking into this area for about 9 to 10 years," says lead author Timothy Wang, MD, the Dorothy L. and Daniel H. Silberberg Professor of Medicine and a gastroenterologist at Columbia University, noting that the research came out of a National Cancer Institute consortium known as the Tumor Microenvironment Network, which launched in 2006.…”
mentioning
confidence: 99%